THE EFFECT OF CHORAL READING STRATEGY ON TEACHING STUDENTS READING COMPREHENSION - Sulung, Yohanis Yafet; palengkahu, Noldy; Tuerah, Ignatius Javier (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This study aims to determine the reading comprehension of SMP BEREA Tondano eighth-grade students who use the choral reading approach, as well as the reading comprehension of SMP BEREA Tondano second-grade students who do not use the choral reading technique. Those who are taught using a choral reading technique have superior reading comprehension than those who are taught using a non-choral reading strategy. The research method is experimental, with one experimental and control class using the pre-test and post-test procedure. The population for this study is 20 students from the second class of SMP BEREA Tondano in the year 2020. The findings of this study suggest that students who employ the choral reading approach get higher reading comprehension scores than those who do not. Keywords : Choral reading, experiment, reading, comprehension, EFL